Use of anthropogenic landscapes in a wild Columba livia (Rock Dove) population - Smith, WJ; Portugal, SJ; Jezierski, MT (Oxford University Press, 2024)
Despite the role of many domestic animals as model organisms, our understanding of their undomesticated conspecifics is comparatively poor. This limits our ability to infer the eco-evolutionary context of phenomena studied in the laboratory and to explore domestication. The domestic pigeon’s wild form is the Rock Dove (Columba livia). By studying 5 global positioning system–tagged wild Rock Doves in Scotland’s Outer Hebrides, we present the first individual-level assessment of undomesticated Rock Dove movements, revealing extensive use of anthropogenic habitats in both a roosting and foraging context. This association with humans provides tantalizing opportunities for research into the pre-domestication human–pigeon relationship. More generally, this work highlights the value of researching laboratory model species in nature.